2021
DOI: 10.1101/2021.05.19.444774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation rate of SARS-CoV-2 and emergence of mutators during experimental evolution

Abstract: "How predictable is evolution?" is a key question in evolutionary biology. Experimental evolution has shown that the evolutionary path of microbes can be extraordinarily reproducible. Here, using experimental evolution in two circulating SARS-CoV-2, we estimate its mutation rate and demonstrate the repeatability of its evolution when facing a new cell type but no immune or drug pressures. We estimate a genomic mutation rate of 3.7x10^-6 nt^-1 cycle^-1 for a lineage of SARS-CoV-2 with the originally described s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The spike of SARS-CoV-2 evolves faster than other genomic regions via both point mutations [ 41 , 42 ] and recombination [ 43 ]. Therefore, several evolutionary scenarios for the future trajectory of SARS-CoV-2 [ 44 ] show that this pandemic may not yet be over.…”
Section: Discussionmentioning
confidence: 99%
“…The spike of SARS-CoV-2 evolves faster than other genomic regions via both point mutations [ 41 , 42 ] and recombination [ 43 ]. Therefore, several evolutionary scenarios for the future trajectory of SARS-CoV-2 [ 44 ] show that this pandemic may not yet be over.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 genomic mutation rate in humans is estimated at 0.8-2.38 × 10 -3 nucleotide substitutions per site per year largely based on analysis of sequencing data archived in public repositories [5]. Emerging studies are attempting to confirm this mutation rate using experimental investigations [6]. By comparison, mutations rates for influenza A virus and Middle East respiratory syndrome CoV (MERS-CoV) are 2.3 × 10 -3 and 1.12 × 10 -3 nucleotide substitutions per site per year, respectively [7][8][9][10].…”
Section: Replication-induced Genomic Errorsmentioning
confidence: 99%
“…Human CoVs (HCoV)-OC43 and HCoV-229E have an average mutation rate of 3-6 × 10 -4 nucleotide substitutions per site per year [8]. Emerging experimental data suggest that SARS-CoV-2 is capable of mutating and accumulating changes when facing a new cell type, albeit in the absence of immune surveillance in a singlecell-type infection model [6]. A clinical study also reported the rapid evolution of SARS-CoV-2 variants in the presence of antibodies from convalescent plasma therapy [11].…”
Section: Replication-induced Genomic Errorsmentioning
confidence: 99%
“…Mutations that either increase transmissibility or render immune escape typically result in an evolutionary gain and might quickly become dominant. The global prevalence of SARS-CoV-2, results in a high number of mutations, even though the mutation rate of the virus itself is considered to be low (0.1 per genome per infection cycle) [ 2 ]. The B.1.617.2 (Delta) lineage emerged in India during the spring of 2021 and has since become one dominant variant globally [ 3 ].…”
Section: Introductionmentioning
confidence: 99%